2022
DOI: 10.1016/j.breast.2022.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Psychoeducation for breast cancer: A systematic review and meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 63 publications
1
19
0
3
Order By: Relevance
“…Education, training, and behavioral changes that assist patients in acquiring a better knowledge of dialysis and adopting healthy living habits have been shown to increase patient conformity with the treatment [ 15 , 16 ]. Few studies have explicitly tested conformity and published the conformity rate [ 17 ]; however, the interdialytic weight gain (IDWG) and serum phosphorus level are the most often reported indicators for complete conformance. Conformity requirements have been published by the WHO [ 18 ].…”
Section: Pruritus Mechanisms and Associated Causesmentioning
confidence: 99%
“…Education, training, and behavioral changes that assist patients in acquiring a better knowledge of dialysis and adopting healthy living habits have been shown to increase patient conformity with the treatment [ 15 , 16 ]. Few studies have explicitly tested conformity and published the conformity rate [ 17 ]; however, the interdialytic weight gain (IDWG) and serum phosphorus level are the most often reported indicators for complete conformance. Conformity requirements have been published by the WHO [ 18 ].…”
Section: Pruritus Mechanisms and Associated Causesmentioning
confidence: 99%
“…Therefore, it is necessary to monitor the levels of psychological distress regularly and refer them to mental health experts, if necessary. In addition, since psychosocial intervention effectively alleviates psychological distress [ 35 ], it is desirable to include psychosocial interventions in the integrated treatment plan for cancer survivors, beginning at the end of primary treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While several meta-analyses have summarized the efficacy of psychological interventions in breast cancer patients, [27][28][29][30][31][32][33][34] our study is the first focusing particularly on various therapeutic approaches for women with non-metastatic breast cancer that are applied in a group setting. Therefore, we adopted a broad approach to comprehensively review the evidence on existing interventions in the field.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…In addition, mindfulness‐based therapy which is usually conducted in groups showed significantly positive effects on anxiety, depression, fatigue, and various other outcomes (7 studies) in comparison to standard care/waitlist conditions 32 . Evidence on psychoeducational groups (14 studies) showed significantly positive, but considerably heterogeneous effects of on depression, anxiety, and quality of life in comparison to standard care and other treatments 33 . In a review of psychosocial interventions for pain in breast cancer patients and survivors, supportive group therapy showed a homogeneous, very small yet significant effect on pain reduction (11 studies) 34 …”
Section: Introductionmentioning
confidence: 99%